(No) Patent, No Cash? A Risk Perception Perspective on the Investment Attitude of Managers Toward Patents1. (February 2014) - Knockaert, Mirjam; Huyghe, Annelore; Clarysse, Bart
Abstract Not all venture capital investors value patents during the selection process in the same way; the majority, but not all, value patents positively.